Map of the total longitudinal conductivity of the sedimentary cover of the Dnieper-Donets depression and Donbas - Logvinov, I.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the basis of the interpretation of the 1D and 2D data of magnetotelluric investigations at about 260 points, the map of the total longitudinal conductivity of the surface sediments of the Dnieper-Donets depression and Donbas is built. It has been harmonized with that on the territory of the Pripyat Trough, the Ukrainian Shield, and the Voronezh massif. The map allows one to assess the lithological characteristics and the resistance of individual complexes of the sedimentary cover.